Cognitive profile of junior college students - Lim, Li Lian. (2008)
The quest for "Academic Excellence", the teachers' calling to serve as effective teachers in this noble profession, the need to prepare our students to meet the challenges of the 21* Century and the recent findings which show that learning styles ( and in particular, cognitive styles ) are related to academic achievement are some reasons why this study is undertaken.